Plasma lipids and XbaI polymorphism on APOB-100 gene in a group of children and their parents (Revista de Investigaciones Universidad del Quindío, 2010)
Introduction: Some studies have shown association between XbaI polymorphism of apolipoprotein B (apoB) gene and serum levels of lipids and apolipoprotein B, but not in others. Objective: to determine the relationship between plasma lipids, apoB, XbaI polymorphism in a group of boys and girls between 4 and 18 years and their parents. Methods: We studied 63 children and 85 parents. The children were divided into two groups: children with hypercholesterolemia (CHC), total cholesterol (TC)>175 mg/dl and children without hypercholesterolemia (SHC), TC
Keywords: Apolipoprotein B; XbaI polymorphism; lipids profile; children; cholesterol